The Czech and German culture, a project management Industry 4.0 case study - Kinda, Ladislav; Brunet-Thornton, Richard; Homola, Heinrich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
This thesis primarily discusses three topics. The first one is national culture and its relationship with business culture in a given nation. A wide range of definitions with diverse dimensions of culture definition is identified. In the second part, the basic concepts from the field of project management are defined. For this, the internationally recognized methodology of PMI is employed. The concepts and terms defined include project, project manager, scope and the role of company strategy in project management. The last literature research part briefly defines Industry 4.0 and related technologies. These three topics are then used as a setting for two case studies, aiming to provide practical application for the previously defined concepts.
Vedoucí práce: Richard Brunet-Thornton
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses